Enhanced Visible Light Photocatalytic Activity for TiO2 Nanotube Array Films by Codoping with Tungsten and Nitrogen - Min Zhang; Juan Wu; DanDan Lu; Jianjun Yang (International Journal of Photoenergy)
A series of W, N codoped TiO2 nanotube arrays with different dopant contents were fabricated by anodizing in association with hydrothermal treatment. The samples were characterized by scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and ultraviolet-visible light diffuse reflection spectroscopy. Moreover, the photocatalytic activity of W and N codoped TiO2 nanotube arrays was evaluated by degradation of methylene blue under visible light irradiation. It was found that N in codoped TNAs exists in the forms of Ti-N-O, while W exists as W6+ by substituting Ti in the lattice of TiO2. In the meantime, W and N codoping successfully extends the absorption of TNAs into the whole visible light region and results in remarkably enhanced photocatalytic activity under visible light irradiation. The mechanism of the enhanced photocatalytic activity could be attributed to (i) increasing number of hydroxyl groups on the surface of TNAs after the hydrothermal treatment, (ii) a strong W-N synergistic interaction leads to produce new states, narrow the band gap which decrease the recombination effectively, and then greatly increase the visible light absorption and photocatalytic activity; (iii) W ions with changing valences in all codoped samples which are considered to act as trapping sites, effectively decrease the recombination rate of electrons and holes, and improve the photocatalytic activity.